Distracted generation (?) : technology use, texting and driving in South Africa - Kgasago, Tshepho Justice (My University, 2017)
The use of communication technologies has brought changes to our daily ways of doing things. Youth use technology for different purposes at different locations. As technology grows everyday with various advantages, its benefits come along with some disadvantages. Road accidents are one of the major problems that South Africa experiences. The focus of this study was to explore the danger of texting and driving and its potentials for road accidents. This research focused on the negative impact of technology, mainly technological distraction, while driving. Broadly, this research looks at the social and cultural impact of texting and mobility, with specific focus on distracted driving. This study is significant in the social analysis of technology use and distraction; this significance is made more important considering that there is very limited study of this social issue in South Africa. The always-available communication culture (such as texting while driving) should be viewed as a problematic phenomenal. For data collection, the researcher conducted a survey with adults and youth drivers to explore the perceptions and attitudes of drivers towards cell phone use, texting and driving. The researcher also conducted roadside observations of drivers to investigate the occurrence of distracted driving due to technology use, and interviews were conducted with Traffic Officers to share their professional experience on observing incidences of texting and driving. The study reveals that technology use, texting and driving is a common problem among young drivers, while adults tend to be more careful and engage less in this activity. Aspect of the findings of the study shows that 60% of drivers report that they have sent a text while driving. Moreover, the study explores ways of curbing cell phone use texting and driving on South African roads. There should be more research on distracted driving and technology use, so that more suggestions on how to curb technology use while driving can be offered
Thesis (M.A. (Communication Studies)) -- University of Limpopo, 2017
Keywords: Technological distraction; Distracted driving; Texting and driving; Always-available communication culture; Road accidents; Technological determinism; Communication and technology; Technology -- Information services; Text messaging (Cell phone systems); Traffic accidents; Traffic safety